DIAGNOSING PRIMARY PUPILS’ LEARNING OF THE CONCEPT OF AFTER IN THE TOPIC TIME THROUGH KNOWLEDGE STATES BY USING COGNITIVE DIAGNOSTIC ASSESSMENT (Malaysian Journal of Learning and Instruction, 2017)
Purpose â€“ Knowledge state specifies pupilsâ€™ mastery level and informs about their strength and weaknesses in the tested domain. This study attempted to diagnose primary pupilsâ€™ learning the concept of after through their knowledge states by using Cognitive Diagnostic Assessment (CDA). Methodology â€“ This study employed a survey research design to gauge pupilsâ€™ knowledge states for the concept of finding the date after a specific number of days from a given date [abbreviated as the concept of after]. Quantitative data from the pupilsâ€™ pattern of response to the items in Cognitive Diagnostic Assessment (CDA) were collected and analyzed. Items in the CDA were designed by three experienced Mathematics Education researchers and content validated by a panel of seven expert primary mathematics teachers. It was then administered to 238 Grade Six pupils from 11 primary schools in Penang, Malaysia. The pupilsâ€™ item responses were interpreted into knowledge states and mastery levels. Findings â€“ The overall analysis showed that there were 18 knowledge states diagnosed in the concept of after. This large number of knowledge states indicated the specificity of pupilsâ€™ mastery level and thus provided detailed information about their strengths and weaknesses in the concept of after. The findings of this study imply that primary pupils face different levels of difficulty when they are learning the topic of Time. Significance â€“ This method of diagnosing pupils knowledge in terms of mastery level of each attribute tested is different from a conventional diagnostic test which provides only the final score for each pupil. By knowing the pupils knowledge states, teachers can make use of this fine-grained information to enable them to carry out differentiated instructional planning and other remedial work more effectively. Pupils can also use this information to monitor their own learning by maintaining their strengths and overcoming their weaknesses to cope with their own studies.